2015
DOI: 10.1159/000439535
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NY-ESO-1 in Triple-Negative Breast Cancer Is Associated with Tumor-Infiltrating Lymphocytes and a Good Prognosis

Abstract: Objectives: Accumulating evidence suggests that immunotherapy has great potential for treating triple-negative breast cancer (TNBC). We analyzed the expression of NY-ESO-1, which is a potent immunogenic cancer testis antigen, and its association with clinicopathological factors in large cohorts of breast cancer patients. Methods: A total of 623 consecutive breast cancer patients who underwent surgery between 1993 and 1998 and 612 TNBC patients who underwent surgery between 2004 and 2010 at Asan Medical Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…We decided to examine the expression of the NY-ESO-1 gene in patients with lymphoma, as it is a CTA present in various types of cancer and is associated with clinical factors such as poor prognosis and lower survival. [18][19] We confirmed that NY-ESO-1 gene expression is associated with the advanced stage of the disease, changes in the levels of LDH and the IPI, and survival rates. In DLBCL, there are no reports of an association between the expression of this gene and clinical parameters.…”
supporting
confidence: 63%
“…We decided to examine the expression of the NY-ESO-1 gene in patients with lymphoma, as it is a CTA present in various types of cancer and is associated with clinical factors such as poor prognosis and lower survival. [18][19] We confirmed that NY-ESO-1 gene expression is associated with the advanced stage of the disease, changes in the levels of LDH and the IPI, and survival rates. In DLBCL, there are no reports of an association between the expression of this gene and clinical parameters.…”
supporting
confidence: 63%
“…This would explain the lack of association with CD8 positive cells, unlike the situation in IDC, where CT antigen expression often correlates with CD8 TIL infiltration [15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…Early clinical data and assays in some respects support the rationale for further investigations of SP17 for tumour vaccines [ 157 ]. NY-ESO-1 expression is an independent good prognostic factor (p = 0.046) in TNBC and leads to a high humoural immune response associated with higher TILs [ 158 , 159 ]. Therefore, the detection of NY-ESO-1 expression in TNBC might be useful for selecting patients who may benefit from cancer vaccination therapy.…”
Section: Cancer Vaccinementioning
confidence: 99%